Movable type printing method to synthesize high-entropy single-atom catalysts - Peng Rao; Yijie Deng; Wenjun Fan; Junming Luo; Peilin Deng; Jing Li; Yijun Shen; Xinlong Tian (Nature Communications, 2022)
It is challenging to integrate multi-single metal atoms into one support. In this work, the authors demonstrate the production of high-entropy single-atom catalysts via a movable typing method, which enables the anchor up to eleven metals as highly dispersed single-atom active centers on the carbon support for the oxygen reduction reaction.